A Collocation Method for Solving Fractional Order Linear System - Amir Hosein Refahi Sheikhani; Mahamad Mashoof (Journal of the Indonesian Mathematical Society, 2017)
In this paper we propose the collocation method to achieve the numerical solution of fractional order linearsystems where a Fractional Derivative is defined in the Caputo sense.We use Taylor collocation method,which is based on collocation method for solving fractional differential equation. This method is based onfirst taking the truncated Taylor expansions of the vector function’s solution in the Fractional order linearsystem and then substituting their matrix forms into the system. Using collocation points, we have a systemof linear algebraic equation.The method has been tested by some numerical examples.DOI : http://dx.doi.org/10.22342/jims.23.1.257.